Deviation in Bidel Dehlavi`s lyrics based on Leech`s pattern - Mahdai Sharifieyan; Mostafa Mortezaei (مطالعات زبانی و بلاغی)
Bidel Dehlavi, one of the most famous poets of Safavid era lived in the eleventh and twelfth century .He is considered to be an outstanding poet in the history of Persian literature, so that he is the greatest poet after Jami and Amir Khosrow. Bidel can be known to be the representative of Hindi style in terms of proliferation and detailing as all the features of Safavid scholars and literaries are seen vividly in his works.      Deviation is a remarkable provision to defamiliarity and prominence in the poetry which the ports have used. Bidel has used this provision and theme in his poetry. Based on the formalism mechanism and Leech`s pattern, this research uses descriptive-analytic method to show different types of deviation in Bidel`s lyrics through the library study. The results show that the frequency of semantic deviation in Bidel`s can be seen to exist more.